"ISCHEMIA MODIFIED ALBUMIN: A BIOCHEMICAL MARKER OF ACUTE STROKE" - DR ITISHRI JENA; DR PRAKASH C. MOHAPATRA; DR NIHAR R. MOHANTY (International Journal of Pharma and Bio Sciences, 2016)
Stroke is one of the leading causes of death and disability worldwide. Still there is no cost effective test available as a marker of this disease. Ischemia modified albumin (IMA) is a relatively new biomarker of ischemic events. It was recently demonstrated that IMA levels also increase in acute stroke. Therefore this study was undertaken to evaluate the role of IMA in acute stroke and to find out its correlation with oxidative stress. 33 hemorrhagic stroke patients and 35 thrombotic stroke patients were taken as cases and compared with 36 age and sex matched controls. Serum IMA and MDA along with other routine biochemical parameters were estimated both in cases and controls. The results were analyzed statistically. Serum IMA values were significantly increased both in hemorrhagic and thrombotic stroke cases in comparison to controls (p-value Ë‚0.0001). A significant positive correlation was found between serum IMA and MDA levels of stroke cases (r-value 0.88, p-value Ë‚0.0001). Thus we concluded that IMA generated during ischemia and reperfusion is also raised in acute stroke cases and can be used as a biomarker of acute stroke